Definition of the Portuguese frameworks with international relevance as an input for the European geological heritage characterisation - Brilha, J. B. (2005)
This work constitutes the first contribution for the systematisation of the geological heritage knowledge in Portugal, following the international recomendations for the characterisation of geological heritage (IUGS, ProGEO). The application of the ProGEO methodology has resulted on the creation of fourteen frameworks with international relevance, established by consensus among the Portuguese geological community. The description of each category in this paper is not exhaustive and just the most relevant scientific settings are presented. The following are the three key outcomes of this work: i) At a national level, the most important geosites are identified, indicating where geoconservation efforts should be prioritised through scientific justification; ii) At a regional level, conditions have been developed to foster dialogue with Spanish colleagues in order to create Iberian frameworks; iii) At an international level, is now possible to integrate Portuguese geosites in the global inventories promoted by IUGS, UNESCO, and ProGEO.